Explanatory Factors of the Capital Structure - Marta Silva; Luís Pereira Gomes; Isabel Cristina Lopes (Ital Publication, 2020)
This paper presents an empirical study of the capital structure of Portuguese companies where the main objective is to find key explanatory factors for indebtedness decisions. The relations between indebtedness and its determinants are tested in the light of the Trade-Off Theory and the Pecking-Order Theory. The motivation of this work was to contribute to the scientific research on the influential determinants of the capital structure and to deepen the knowledge of the Portuguese market. The quantitative methodology is used, through an econometric model for panel data using accounting information of 55 Portuguese companies between 2014 and 2016. Statistical tests such as the F test, the Lagrange Multiplier Breusch-Pagan test and the Hausman test were used to identify the most appropriate method of estimation, which resulted in a panel data model with random effects for individuals. The findings of this study suggest that indebtedness have a positive relation with tangibility and the size of the company, which supports the Trade-Off Theory. However, the positive relationship with the non-debt tax benefits suggests the importance of taxes, contrary to Trade-Off Theory. The negative relationship with cash flows, coupled with the positive relationships between size and growth opportunities, suggest the use of funding only when internal funds become insufficient, supporting the Pecking-Order Theory. The general results support that both theories partially explain the financing decisions of Portuguese companies. Doi: 10.28991/esj-2020-01249 Full Text: PDF